2020
DOI: 10.1016/j.joule.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Direct Recycling of Lithium-Ion Battery Cathodes by Targeted Healing

Abstract: A paradigm-shift lithium-ion battery recycling method based on defect-targeted healing can fully recover the composition, structure, and electrochemical performance of spent LiFePO4 cathodes with various degradation conditions to the same levels as that of the pristine materials. Such a direct recycling approach can significantly reduce energy usage and greenhouse gas emissions, leading to significant economic and environmental benefits compared with today's hydrometallurgical and pyrometallurgic methods. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
236
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 344 publications
(281 citation statements)
references
References 46 publications
(55 reference statements)
2
236
0
1
Order By: Relevance
“…As previously mentioned, direct recycling poses a method with greater economic and environmental benefits. [111,112] Recent works demonstrated the possibility of directly recycling LFP [112] and LMO [111] cathodes, in which life-cycle analysis showed a reduction in both GHG emissions (ca. 70%) and energy usage (> 75%).…”
Section: Recyclingmentioning
confidence: 99%
“…As previously mentioned, direct recycling poses a method with greater economic and environmental benefits. [111,112] Recent works demonstrated the possibility of directly recycling LFP [112] and LMO [111] cathodes, in which life-cycle analysis showed a reduction in both GHG emissions (ca. 70%) and energy usage (> 75%).…”
Section: Recyclingmentioning
confidence: 99%
“…Moreover, the pre‐edge peak can be related to Fe 1s–3d transitions [29] . From the inset of Figure 6 e, compared with pristine LFP, the pre‐edge of the LFP electrode with blank electrolyte had shifted in a positive direction (from peak A to B), which indicated that part of Fe 2+ was oxidized to Fe 3+ due to Li vacancy defects [30] . In addition, a positive shift illustrated a lower electron density in the Fe sites [31] .…”
Section: Resultsmentioning
confidence: 95%
“…Finally, metal salts are to be precipitated and re-synthesized to produce new active materials [48,52]. Alternatively, the anode and cathode active materials can be reconditioned by means of purification processes, lithium enhancement, and functionalization [47,51,[77][78][79]. Direct reconditioning has the advantage of being a fast and less energy-consuming process, but it cannot directly adapt the cathode chemistry to new developments.…”
Section: Circular Economy In the Context Of Battery Productionmentioning
confidence: 99%